Effect of electrode geometric parameters on droplet translocation in digital micro-fluidic biosensor - Yogarajan, M.P.; Ibrahim, F.; Soin, N. (2008)
This paper reports a study of an electrowettingon-dielectric (EWOD) biochip capable of droplet translocation. The study composed of an analytical analysis, observed the switching rate of droplet in variation the electrode width, electrode pitch, electrode thickness. It has been shown that at a fixed voltage and other design geometries, the switching rate of a water droplet is proportional to the electrode thickness and size and inversely proportional to electrode pitch. This results can be used to characterize the droplet translocation for a reprogrammable biochip. Â© 2008 Springer-Verlag.